The role of radio-chemotherapy in the treatment of patients with advanced vulvar cancer - Jońska-Gmyrek, Joanna; Gmyrek, Leszek; Krynicki, Ryszard; Lindner, Bogusław; Staniaszek, Jagna; Dańska-Bidzińska, Anna; Bidziński, Mariusz (Menopause Review/Przegląd Menopauzalny, 2007)
Vulvar cancer is a rare neoplasm. It accounts for about 2.5-5% of all gynaecological malignancies [1]. In Poland there are about 350 new cases diagnosed and over 200 deaths, noted per year, due to vulvar cancer. This malignancy affects most frequently postmenopausal women, aged over 60, very often burdened with other diseases, such as coronary disease, hypertension, and diabetes. The most important prognostic factors in squamous cell vulvar carcinoma are: regional lymph nodes status, and tumour volume. Vulvar cancer spreads through direct expansion into adjacent organs, such as the vulva, urethra or anus, or to the regional lymph nodes. The risk of dissemination within the circulatory system is insignificant. Because a significant number of vulvar cancer patients in Poland are diagnosed in an advanced stage of the disease, the optimal treatment modality, which would spare functionally important organs, such as the urethra, urinary bladder and anus, is very important. Because surgical treatment of the disease in this stage would require extensive resections, this treatment modality is not widely accepted. To devise the optimal treatment modality, sparing functionally important organs, radio-chemotherapy in advanced vulvar cancer is the subject of a great number of studies.